Effect of Crystalline and Double Helical Structures on the Resistant Fraction of Autoclaved Corn Starch with Different Amylose Content. (20th April 2020) - Soler, Adrian; Mendez‐Montealvo, Guadalupe; Velazquez‐Castillo, Rodrigo; Hernández‐Gama, Regina; Osorio‐Diaz, Perla; Velazquez, Gonzalo
Abstract: The aim of this work is to investigate the effect of the crystalline and the double helical structures on the resistant starch (RS) fraction of autoclaved corn starch with different amylose content. Normal (NS) and high amylose (HS) corn starches are modified by autoclaving at 105, 120, and 135 °C. Autoclaving causes structure disorganization in NS or structural rearrangements in HS. The RS increases from 2.1% to 5.5% in NS autoclaved at 135 °C and from 12.7% to 30.2% in HS autoclaved at 120 °C. The RS is correlated to T e in NS ( r = 0.73) and HS ( r = 0.79), indicating that the double helical crystallites with high thermal stability ( T e = 176.8–193.6 °C) are responsible for the increase of RS. In autoclaved HS, the RS is correlated to the degree of order (DO) ( r = 0.82) suggesting that the strengthened associations between double helices contribute to the RS formation. The results lead to the possibility of controlling the resistance by modifying the starch structure using autoclaving process. This research highlights that the organization of the double helical structure is more important than the crystalline order to form resistant corn starch. Abstract : Resistant starch (RS) is a functional compound. Normal and high amylose corn starches are autoclaved to obtain RS. Formation of RS depends more on the organization of the double helical order than on the crystalline structure. Understanding the structural factors determining the formation of RS could help to tailor the properties of autoclaved starch when used as an ingredient.